Analisis Corporate Social Responsibility (CSR) Ritel Modern Skala Besar terhadap Peningkatan Kinerja Pemasaran, Keuangan dan Daya Tahan UKM - Utami, Chr. Widhya (Kajian Manajemen dan Bisnis, 2010)
Corporate Social Responsibility (CSR) is a form of large-scale industrial responsibility for the conduct of cultural adaptation with social environment. CSR is a program, which includes various forms of activities that may be a solution for social problems which include the creation of employment opportunities , health, education, economy and environment. The purpose of this study was to Know and analyze the effect of the implementation of the CSR program conducted on the performance of major retail marketing, financial performance and endurance of the SME business. A number of 149 SMEs suppliers of large scale retail respondents.